Internalisasi Budaya Siri’ Na Pacce dalam Membangun Karakter Mahasiswa di Perguruan Tinggi - Syamsunardi Syamsunardi (LaGeografia, 2022)
Local culture is a source of the richness and diversity of Indonesian culture. Internalization of local culture in formal education is needed to build student character. The aims of this study were: 1) to find out the meaning of the siri' na pacce culture of the Makassarese tribe, 2) to internalize the siri' na pacce culture to students. This study uses an ethnographic approach. The results of this study: 1) siri' is defined as shame, the word na as a connecting word is interpreted as "and" or "with" and pacce is defined as concern for people as evidenced by concrete actions, 2) the internalization of siri' na pacce culture is carried out on students Department of Geography FMIPA UNM through cultural geography courses with local cultural material.AbstrakBudaya lokal sumber kekayaan dan keragaman budaya Indonesia. Internalisasi budaya lokal pada pendidikan formal perlu untuk membangun karakter Mahasiswa. Tujuan penelitan: 1) untuk mengetahui makna budaya siri’ na pacce suku Makassar, 2)  menginternalisasikan budaya siri’ na pacce pada mahasiswa Perguruan Tinggi. Penelitian ini menggunakan metode kualitatif pendekatan etnografi. Hasil penelitian ini: 1) budaya siri’ dimaknai sebagai rasa malu, kata na sebagai kata penghubung dimaknai “dan” atau “dengan” dan pacce dimaknai rasa peduli terhadap orang kesusahan dibuktikan dengan tindakan konret, 2) internalisasi budaya siri’ na pacce dilakukan pada mahasiswa Jurusan Geografi FMIPA UNM melalui matakuliah geografi budaya dengan materi budaya lokal.